The Relationship between Knowledge and Family Support with Tb Patient Drinking Compliance in Kudungga Hospital - Siti Fatimah Djaja PN; Joko Sapto Pramono; Tini (Formosa Journal of Science and Technology, 2023)
Tuberculosis is an infectious disease mostly caused by Mycobacterium tuberculosis. There are various species of Mycobacterium, including Mycobacterium africanum, Mycobacterium bovis and Mycobacterium leprae, known as Acid Resistant Bacteria (BTA). The recovery or success of this treatment is determined by several factors, especially adherence to taking medication. Family support greatly supports the successful treatment of pulmonary TB patients by always reminding sufferers to take medicine, deep understanding of patients who are sick and encouraging them to remain diligent in treatment. This study used a purposive sample technique with a cross-sectional study design. The sample size in this study was 76 people. The results of the statistical test using the chi-square test obtained a p-value = 0.033 (Knowledge on Medication Compliance), p-value = 0.002 (Family Support with Medication Adherence). There is a relationship between Knowledge and Family Support with Compliance with Taking Medication for TB Patients at Kudungga Hospital.